PESAGUAN DAYAK CULTURE: TENTOBUS TRADITIONAL CEREMONY - Tindarika, Regaria; Satrianingsih, Aline Rizky Oktaviari; Aditya, Mega Cantik Putri; Sulissusiawan, Ahadi (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
The Pesaguan Dayak ethnic has various types of culture and customs within it. One of the cultures it has is in the form of traditional ceremonies. The Tentobus Traditional Ceremony has a series of activities that have been arranged systematically from start to finish. This research aims to describe the processions contained in the Tentobus Traditional Ceremony considering that carrying out traditional ceremonies has its own applicable rules and procedures. The rules and procedures for carrying out traditional ceremonies in an ethnic group are a reflection of the society that has them. The data was obtained using data collection techniques such as direct observation, in-depth interviews, documentation and literature studies related to the object and focus of the research. The results of this research are that the Tentobus traditional ceremony procession was held for 2 consecutive days. The traditional ceremonial procession on the first day consists of tentobus; penyorahan sensarang; betare; and menanam ancak. Meanwhile, the Tentobus traditional ceremony procession of the Dayak Pesaguan ethnic on the second day consisted of the Besogak Dance; Makan Betanggai;, and Mengerurutan Payung Langit.